2021
DOI: 10.31219/osf.io/t8wza
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of AYUSH 64 as add-on therapy in early stage COVID 19 - An open-label randomized controlled pilot study

Abstract: Background: Efficacy of AYUSH 64 has been proven in fever and influenza-like illness earlier. Hence it was felt it should be evaluated in COVID 19 which has similar symptom complex. Aim: To evaluate the clinical efficacy of AYUSH 64 as an add-on to standard care in early stage COVID-19 patients. Materials and methods: After obtaining IEC permission, a single centre, randomized, open labelled, controlled, pilot study was undertaken. Asymptomatic to mild COVID 19 (RT-PCR positive) patients, who gave written info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Other contemporary studies of AYUSH-64 for COVID-19 have also reported early clinical recovery and reduction in the levels of pro-inflammatory markers in asymptomatic and mild COVID-19 cases [32][33]. Reduction in the levels of pro-inflammatory markers indicates that AYUSH-64 could possibly arrest the inflammatory cascade, thereby seize or stop the progression of the disease to the severe or critical stage.…”
Section: Discussionmentioning
confidence: 89%
“…Other contemporary studies of AYUSH-64 for COVID-19 have also reported early clinical recovery and reduction in the levels of pro-inflammatory markers in asymptomatic and mild COVID-19 cases [32][33]. Reduction in the levels of pro-inflammatory markers indicates that AYUSH-64 could possibly arrest the inflammatory cascade, thereby seize or stop the progression of the disease to the severe or critical stage.…”
Section: Discussionmentioning
confidence: 89%
“…One report was excluded during the data extraction process, which used AYUSH interventions as a comparator, 16 finally 12 manuscripts were included. [17][18][19][20][21][22][23][24][25][26][27][28] Detail description of the study selection and elimination process has been depicted in figure 1. All the articles were in the English language only.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among included studies of the therapeutic domain, 2 RCTs examined the benefit of AYUSH-64, 17,18 2 studies (1 RCT, 1 NRSI) of Guduchi Ghanavati, 19,20 each one RCT on different multiple Combinations of Ayurveda medicines (coded as AYUSH regimen-I, II, III, IV, V, VI, and VII). [21][22][23][24][25][26] AYUSH Regimen III and IV were examined in a single RCT.…”
Section: Figure 1: Prisma Flow Chartmentioning
confidence: 99%
See 2 more Smart Citations